2016
DOI: 10.1159/000448553
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Prediction Models for Near Adult Height in Children with Idiopathic Growth Hormone Deficiency Treated with Growth Hormone: A Belgian Registry Study

Abstract: Background/Aim: To validate prediction models for near final adult height (nFAH) by Ranke et al. [Horm Res Paediatr 2013;79:51-67]. Methods: Height data of 127 (82 male) idiopathic growth hormone (GH)-deficient children, treated with GH until nFAH, were retrieved from the database of the Belgian Society for Pediatric Endocrinology and Diabetology (BESPEED). nFAH was predicted after first-year GH treatment, applying prediction models by Ranke et al. Bland-Altman plots and Clarke error grid analyses were perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 23 publications
(36 reference statements)
2
7
0
Order By: Relevance
“…However, although the treatment response to MPHD is better, FAH-SDS can be similar to that seen in patients with IGHD (GHD) due to more severe GHD, shorter initial height, and the presence of other hormone deficiencies accompanying GHD ( 22 ). In agreement with previous reports, both delta height SDS and FAH-SDS were higher in patients with MPHD than patients with IGHD ( 6 , 14 , 15 , 16 , 18 ). This was attributed to younger age for the onset of the treatment, longer duration of treatment, lower bone age, and lower IGF1 SDS as well as peak GH values in the GH stimulation test.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…However, although the treatment response to MPHD is better, FAH-SDS can be similar to that seen in patients with IGHD (GHD) due to more severe GHD, shorter initial height, and the presence of other hormone deficiencies accompanying GHD ( 22 ). In agreement with previous reports, both delta height SDS and FAH-SDS were higher in patients with MPHD than patients with IGHD ( 6 , 14 , 15 , 16 , 18 ). This was attributed to younger age for the onset of the treatment, longer duration of treatment, lower bone age, and lower IGF1 SDS as well as peak GH values in the GH stimulation test.…”
Section: Discussionsupporting
confidence: 93%
“…In an international study in 1619 patients with IGHD the FAH-SDS was reported to be -1.4 SD ( 6 ). Cappa et al ( 16 ), Rachmiel et al ( 17 ), Straetemans et al ( 18 ), Carel et al ( 19 ), and Thomas et al ( 20 ) reported -0.86, -1.04, -1.74, -1.6, -0.8 FAH-SDS in patients with IGHD, respectively. In all these studies, although the GH treatment dose was similar or lower than our study in IGHD groups, FAH-SDS were better than in our study, and delta height SDS was similar ( Table 4 ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The response to GH therapy in children has been traditionally expressed in terms of growth velocity (GV) measured as cm/year. In our cohort of patients, after one year of treatment, the average GV was 9.4 ± 3.5 cm, similar to that reported in larger studies [22,36]. The difference between near-adult height SDS and mid-parental target height SDS is, however, considered as the best indicator of whether an individual has achieved his/her height potential [10].…”
Section: δIgf-1 Z-supporting
confidence: 88%
“…However, the predicted FAH following a short period of treatment is dynamic and cannot reflect the actual FAH. Owing to the heterogeneity of the treated ISS populations and the individualization of treatment, only a few randomized trials with small sample sizes have observed ISS until FAH [6][7][8][9][10]. A randomized study of FAH typically takes 8 years or more to complete and is often difficult to implement in clinical settings.…”
Section: Introductionmentioning
confidence: 99%